Impacto da implantação do esgotamento sanitário sobre a mortalidade infantil no município de Guanambi – Bahia - Azevedo, Ruy Fernandes de (2019)
Introduction: The child mortality remains high in many countries in the world especially those with low economic and social development conditions, where general living conditions are precarious, as basic sanitation, potable water access and appropriate hygiene practices. The emerging countries, among which is Brazil, obtained a reduction in the child mortality rate on the last decades, due to the increased income of the population, associated to the implementation of the public policies. Objective: The objective from the current study was to evaluate the impact of implementation of the sanitary sewage service on the child mortality rate in the city of Guanambi, southwest of Bahia-Brazil. Methods: It was an exploratory, quantitative, analytical and longitudinal cut study. The data were obtained through surveys in the Municipal Health Department/Basic Care Information Service – SMS/SIAB, in the Department of the Single Health System- DATASUS, in the Brazilian Institute of Geography and Statistics – IBGE and Bahia’s Company of Water and Sanitation – EMBASA, between the months of august 2017 to march 2018, relating to the period between the years 2006 to 2017. Results: The result showed a reduction on the child mortality rate (CMR) between the years of 2006 to 2017, after the implantation of sewage sanitary service. There was a significant reverse linear association (p<0.01) and with high magnitude (r=-0.92) between the child mortality rate and year. Conclusion: The investment in basic sanitation is an important factor in the reduction of child mortality rate, and, therefore, improves the health population indicator.